2020
DOI: 10.1051/0004-6361/201937040
|View full text |Cite
|
Sign up to set email alerts
|

Formation channels of slowly rotating early-type galaxies

Abstract: We study the evidence for a diversity of formation processes in early-type galaxies by presenting the first complete volume-limited sample of slow rotators with both integral-field kinematics from the ATLAS 3D Project and high spatial resolution photometry from the Hubble Space Telescope. Analysing the nuclear surface brightness profiles of 12 newly imaged slow rotators, we classify their light profiles as core-less, and place an upper limit to the core size of about 10 pc. Considering the full magnitude and v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 216 publications
(328 reference statements)
3
39
2
Order By: Relevance
“…Dry mergers lead to SRs that have flatter [Fe/H] profiles due to the effective redistribution of stellar mass during dry mergers (Lagos et al 2018b). Krajnović et al (2020) found that classical slow rotators (which they linked to the dissipation-less galaxy mergers; i.e. dry mergers) have flatter metallicity gradients than other slow rotators in ATLAS 3D , which is in qualitative agreement to what we find in .…”
Section: The Stellar Populations Of Slow Rotatorssupporting
confidence: 90%
See 1 more Smart Citation
“…Dry mergers lead to SRs that have flatter [Fe/H] profiles due to the effective redistribution of stellar mass during dry mergers (Lagos et al 2018b). Krajnović et al (2020) found that classical slow rotators (which they linked to the dissipation-less galaxy mergers; i.e. dry mergers) have flatter metallicity gradients than other slow rotators in ATLAS 3D , which is in qualitative agreement to what we find in .…”
Section: The Stellar Populations Of Slow Rotatorssupporting
confidence: 90%
“…Weijmans et al (2014); Foster et al (2017); Li et al (2018a); Krajnović et al (2018) find that SRs tend to have a higher occurrence of triaxial or prolate intrinsic shapes compared to fast rotators, which are mostly oblate, axisymmetric systems (often with bars). The intrinsic stellar populations of SRs indicate flat α/Fe metallicity radial profiles, uniform old stellar ages, and declining metallicity radial profiles (where the central parts are more metalrich than the outer parts; Kuntschner et al 2010;Bernardi et al 2019;Krajnović et al 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Massive early-type galaxies and some BCGs can acquire cold gas through the cooling of hot gas and/or via cannibalism of a gas-rich satellite and they may undergo episodes of low level star formation at low redshift(Salomé & Combes 2003;O'Dea et al 2008;Hopkins & Hernquist 2009;Struve et al 2010;Young et al 2011;Zubovas & King 2012;Russell et al 2014;Smith & Edge 2017;Russell et al 2019;Krajnović et al 2020). …”
mentioning
confidence: 99%
“…Numerous integral field spectroscopic surveys provide stellar metallicity gradient measurements. Most such surveys of nearby massive galaxies resolve well within once or twice the effective radii (e.g., SAURON, AT-LAS3D, MANGA, SAMI; Kuntschner et al 2010;Krajnović et al 2020;González Delgado et al 2015;Martín-Navarro et al 2018;Bernardi et al 2019;Ferreras et al 2019a;Oyarzún et al 2019), yet few probe beyond the cores because of the limited field of view. Thus we compare our integrated stellar metallicities with results from the MASSIVE and CALIFA surveys that provide gradient measurements to the largest spatial extent, out to ≈ 2.5 r eff .…”
Section: Descendantsmentioning
confidence: 99%